Developing a Rapid and Sensitive Colorimetric Sensor for Detection of Food Adulterant Rhodamine-B in Real Samples - Pratap R.; Das A.; Mishra A.; Chaudhary S.; Singh Parmar A. (My University, 2025)
Rhodamine B (Rh−B) is a well-known carcinogenic agent with potential health risks, yet it is frequently used as a food adulterant in developing countries. This study presents the synthesis and characterization of a Broussonetia Zeylanica extract (BZ-EXT) from a plant for the rapid, efficient, and sensitive colorimetric sensing of Rh−B. The limit of detection (LOD) and limit of quantification (LOQ) were found to be 0.41 μg/mL and 1.31 μg/mL, respectively. We demonstrating superior sensitivity compared to conventional methods using DI water as a solvent. Furthermore, the practical applicability of the developed material was successfully tested in real samples, yielding estimated values of Rh−B are 0.76 μg/mL and 0.52 μg/mL, respectively. The pH dependent colorimetric sensing performance of the BZ-EXT for Rh−B detection was found more efficient at aqueous pH value of 9.2. These results highlight the potential of the BZ-EXT as a promising tool for rapid and sensitive detection of Rh−B food adulteration in real samples. © 2024 Wiley-VCH GmbH.